The Effect Of Use Powtoo Learning Media To Student Learning Motivation On 3rd Grade On Indonesia Subjects At Islamic Elementary School Athirah 1 Makassar - Indah Trismayani Jabir; Rohana Rohana; Amir Pada (Program Studi PGSD FIP UNM, 2021)
This research is an experimental study that aims to determine the significant effect of use powtoon learning media to student learning motivation on 3rd grade on indonesian subjects at islamic elementary school athirah 1 makassar. The independent variable in this study is the use of Powtoon learning media, while the dependent variable is student learning motivation. This research using a quantitative approach and using this type of experimental research with the research design One Group Pretest-Posttest Design. The population in this study were 120 students of third grade of Athirah Islamic Elementary School 1 Makassarfor the academic year 2020-2021. Determination of the sample of this study using a simple random sampling technique, Class III Al-Aziz SD Islam Athirah 1 Makassar as an experimental class as many as 25 people. Data were collected using research instruments in the form of student learning motivation questionnaires, observation and documentation. The data analysis technique used in hypothesis testing is Paired Sample t-test with the help of the IBM SPSS Statistic Version 22 application.The results of measuring student learning motivation comparing the results of pre-test and post-test using Powtoon learning media show that the use of Powtoon learning media has a significant effect on the learning motivation of third grade students of Athirah Islamic Elementary School 1 Makassar.